Mutations in KCNJ5 determines presentation and likelihood of cure in primary hyperaldosteronism. Issue 4 (26th November 2013) - Ip, Julian C. Y.; Pang, Tony C. Y.; Pon, Cindy K.; Zhao, Jing Ting; Sywak, Mark S.; Gill, Anthony J.; Soon, Patsy S.; Sidhu, Stan B.
Abstract Introduction Primary hyperaldosteronism (PA) is a common cause of secondary hypertension. Two recurrent mutations (G151R and L168R) in the potassium channel gene KCNJ5 have been identified that affect the Kir3.4 potassium channel found in the cells of the zona glomerulosa of the adrenal gland. The aim of this study was to determine the prevalence of KCNJ5 mutations in an Australian cohort of patients and to correlate these findings with clinical outcome data, in order to describe the clinical impact on patients who harbour this mutation. Methods Direct Sanger sequencing for KCNJ5 on DNA from adrenal tumour tissue of 83 patients with PA in a cohort study was undertaken and mutation status correlated with clinical outcome data. Results Seventy‐one of 83 patients (86%) had adrenocortical adenomas and 12 patients (14%) had bilateral adrenal hyperplasia. A total of 34 (41%) patients were found to have heterozygous somatic mutations in KCNJ5, G151R and L168R. No germ line mutations were identified. Patients with mutations were predominately female (68% versus 49%) and significantly younger at presentation (48 versus 55 years). When correlated with clinical data, our results demonstrated that patients with KCNJ5 mutations were more likely to be cured following surgery without the requirement for ongoing medications. Conclusions Our findings in a large Australian cohort show that patients with mutations in KCNJ5 present earlier with the signs and symptoms of PA benefit from surgical intervention. Moreover, our results highlight the importance of a thorough workup and management plan for younger patients who present with hypertension.